The paper crane - Bang, Molly (New York : Greenwillow Books, 1985)
A mysterious man enters a restaurant and pays for his dinner with a paper crane that magically comes alive and dances.
Wilson's Children, October 2010.
Elem. School Library Collection, June 2000.
Notable/Best Books (A.L.A.), September 2004.
School Library Journal, August 1997.
Book Links (A.L.A.), July 1995.
Booklist, March 1996.
Keywords: Cranes (Birds) -- Fiction; Restaurants -- Fiction; Cranes (Birds) -- Fiction; Restaurants -- Fiction